Plasmid mediated colistin resistant mcr-1 and co-existence of OXA-48 among Escherichia coli from clinical and poultry isolates: first report from Nepal - Muktan, Bijaya; Thapa Shrestha, Upendra; Dhungel, Binod; Mishra, Bagish Chandra; Shrestha, Nabaraj; Adhikari, Nabaraj; Banjara, Megha Raj; Adhikari, Bipin; Rijal, Komal Raj; Ghimire, Prakash (Gut pathogens, 2020)
Plasmid-mediated resistance to the last-resort drugs: carbapenems and colistin is an emerging public health threat. The studies on the prevalence and co-expression of resistant genes among livestock and human pathogens are rare in Nepal. This is the first study in Nepal exploring the prevalence and co-existence of colistin resistance gene, -1 along with carbapenemase resistance gene, -48 in isolated from poultry and clinical specimens. A total of 240 rectal swabs from chickens of five different poultry farms of Kathmandu valley and 705 mid-stream urine samples from human subjects attending Kantipur Hospital, Kathmandu were collected between August, 2018 and March, 2019. Rectal swabs and urine specimens were cultured. isolated from the specimens were screened for antimicrobial susceptibility testing (AST) using disk diffusion method'. Minimum inhibitory concentration (MIC) of colistin was determined by agar dilution method using 0.5 µg/ml to 32 µg/ml. The isolates were first screened for - followed by screening for - genes using conventional Polymerase chain reaction (PCR). Of the total samples analyzed, was isolated from 31.7% (76/240) of poultry and 7.9% (56/705) of clinical specimens. In AST, 80% (61/76) of from poultry and 79% (44/56) from clinical specimens were MDR. The phenotypic prevalence of colistin resistance in poultry specimens were 31.6% (24/76) and clinical specimens were 21.4% (12/56). In PCR assay, 27.6% (21/76) of poultry and 19.6% (11/56) of clinical isolates had colistin resistant - gene. MICs value of isolates ranged from 4 to 32 (µg/ml) in both clinical and poultry isolates. Prevalence of co-existing carbapenem resistance gene, -48, among colistin resistant -1 positive isolates was 38% (8/21) in poultry specimens and 18.2% (2/11) in clinical specimens. The high prevalence of colistin and carbapenem resistant genes, and their co-existence in plasmid DNA of isolates in this study suggests the possible spread to other animal, human and environmental pathogens. Molecular methods in addition to the conventional diagnostics in laboratories can help in early diagnosis, effective management and control of their potential transmission.